PENGARUH KESADARAN MEREK, LOYALITAS MEREK DAN PERSEPSI KUALITAS TERHADAP MINAT KONSUMEN PADA TOKO SOLO INDAH PEKANBARU - Putra, Rahmat Rial Sal; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research is conducted at Toko Solo Indah Pekanbaru which is located at Kopen Street, Tangkerang Tengah, Marpoyan Damai, Pekanbaru. The purpose of this research is to know how big influence of brand awareness, brand loyalty and perception of quality to consumer interest in Toko Solo Indah Pekanbaru. Samples in this study were taken as many as 100 respondents and the techniques used accidental sampling. The data in this study using survey method through questionnaires filled by consumers. The data obtained from the questionnaire and then processed to then tested through statistics through the SPSS program. Hypothesis testing using simple linear analysis method and multiple linear analysis. From the results of tests conducted indicate that brand awareness, brand loyalty and quality perceptions have a positive and significant impact on consumer interest in Toko Indah Solo Pekanbaru. With R2 value of 0.713. This shows that brand awareness, brand loyalty and quality perception give 71.3% influence on consumer interest in Toko Solo Indah Pekanbaru, while the remaining 28.7% influenced by other variables not examined in this study.Keywords: Brand awareness, Brand loyalty, Quality perception and Consumer Interest